Policy Change im lokalen Migrationsregime der Türkei - Rass-Turgut, Seda (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
This study provides readers with valuable insights into the local adaptation processes of Turkey's migration regime since 2011, particularly in the context of Syrian refugee migration. Through innovative methodological triangulation of text mining, Qualitative Comparative Analysis (QCA), and interviews, local migration policies and the role of international NGOs are comprehensively analysed. The research includes 1,118 administrative documents and numerous interviews to identify changes and patterns in migration governance. An indispensable work for scholars, policymakers, and NGOs, it sheds light on the complex dynamics and political transformations in host countries. The author is an expert on migration policy and local governance in Germany.